Transcriptomic Approach to Lesch-Nyhan Disease - Dauphinot, Luce (2014)
Lesch-Nyhan disease (LND) is an X-linked metabolic disease caused by various mutations in the gene HPRT1 encoding an enzyme of purine metabolism, hypoxanthine guanine phosphoribosyltransferase (HPRT). In its most severe form, LND patients suffer from overproduction of uric acid along with neurological or behavioural difficulties including self-injurious behaviours. To gain more insight into pathogenesis, we compared the transcriptome from human LND fibroblasts to normal human fibroblasts using a microarray with 60,000 probes corresponding to the entire human genome. Using stringent criteria, we identified 25 transcripts whose expression was significantly different between LND and control cells. These genes were confirmed by quantitative RT-PCR to be dysregulated in LND cells. Moreover, bioinformatic analysis of microarray data using gene ontology (GO) highlighted clusters of genes displaying biological processes most significantly affected in LND cells. These affected genes belonged to specific processes such as cell cycle and cell-division processes, metabolic and nucleic acid processes, demonstrating the specific nature of the changes and providing new insights into LND pathogenesis.